Pollen Biology and Biotechnology - Shivanna, K R (New Hampshire : Science publishers, 2003)
The author offers an overview of pollen biology and biotechnology for students and researchers in areas such as reproductive biology, biotechnology, aeropalynology, plant breeding, horticulture, and forestry. Citing more than 1,500 references to pollen research, the text covers topics including advances in understanding pollen tube growth, the use of pollen for gene transfer, and advantages and disadvantages of various pollination systems for production of species limits.
Includes References 237-284p.; Index 285-301p.
Keywords: Biotechnology; Botany; Pollen biology; General Science